Canavanine activates imidazoline I-2 receptors to reduce hyperglycemia in type 1-like diabetic rats. (5th October 2015) - Chang, Chin-Hong; Chao, Pin-Chun; Niu, Ho-Shan; Huang, Gin-Chi; Chen, Li-Jen; Cheng, Juei-Tang
Abstract: Canavanine is a guanidinium derivative that has the basic structure of a ligand for the imidazoline receptor (I-R). Furthermore, canavanine is found in an herb that has been shown to improve diabetic disorders. Thus, the present study was designed to investigate the anti-hyperglycemic action of canavanine in rats with streptozotocin (STZ)-induced type 1-like diabetes. Canavanine decreased hyperglycemia in the STZ-induced diabetic rats, and this action was blocked by the antagonist specific to imidazoline I-2 receptors (I-2R), BU224, in a dose-dependent manner. Additionally, canavanine increased the plasma β-endorphin level, as measured using enzyme-linked immunosorbent assay (ELISA), and this increase was also blocked by BU224 in the same manner. Moreover, amiloride at a dose sufficient to block I-2AR attenuated the actions of canavanine, including the increased β-endorphin level and the antihyperglycemic effect. Otherwise, canavanine increased the radioactive glucose uptake into skeletal muscles isolated from the diabetic rats. Furthermore, canavanine increased the phosphorylation of AMPK measured using Western blot analysis in these isolated skeletal muscles in a dose-dependent manner. Additionally, the insulin sensitivity of the diabetic rats was markedly increased by canavanine, and this action was also blocked by BU224. Overall, canavanine is capable of activating imidazoline I-2R; I-2AR is linked to an increase in the plasma level of β-endorphin, and I-2BR is related to effects on the glucose uptake by skeletal muscle that reduces hyperglycemia in type 1-like diabetic rats. Therefore, canavanine can be developed as effective agent to treat the diabetic disorders in the future. Graphical abstract: Highlights: Canavanine decreases hyperglycemia in type-1 like diabetic rats. This action due to an activation of imidazoline I-2 receptors. Activation of I-2A receptors linked an increase of β-endorphin in plasma. Activation of I-2B receptors enhanced glucose uptake in skeletal muscle.